PERIODONTAL DISEASES AND SYSTEMIC VASCULITIS: A VIEW THROUGH THE PRISM OF INTERDISCIPLINARY STUDIES - T. V. Beketova; E. I. Selifanova (Научно-практическая ревматология, 2018)
The review deals with investigations aimed to examine the relationship between periodontal diseases (PDs) and a chronic autoimmune inflammatory response, the most striking models of which include systemic vasculitis (SV). PDs are associated with systemic inflammation and vascular pathology, which is characterized by endothelial dysfunction and a considerable risk for cardiovascular and cerebrovascular diseases, diabetes mellitus, and autoimmune diseases. The paper also discusses the prospect of interdisciplinary studies focused on the examination of the biological effects of PDs in SV and other rheumatic diseases.